A Study of Buying Behaviour of Customers Towards Branded and Non-Branded Gold Jewellery with Reference to Meerut City - Saxena, Kavita (Journal of Commerce and Trade, 2016)
History of Indian jewellery is as old as the history of the country itself. Around 5000 years ago, the desire to adorn themselves aroused in people, leading to the origin of jewellery. Since then, Indian women and jewellery have gone in hand in hand. There cannot be a women in India, who does not adore herself with minimum jewellery. In fact, jewellery is considered as security and prestige of women in the country. The attraction for jewellery has been great in India that it is no more a craft than an art. In India, gold jewellery is a store of value, a symbol of wealth and status and a fundamental part of the many rituals. In the country’s rural population, a deep affinity for gold goes hand in hand with practical consideration of the portability and security of jewellery as an investment.